Trois générations d'art québécois 1940-1950-1960. - Saint-Martin, Fernande (Montreal : Musée d'Art Contemporain, 1976)
Alleyn, Edmund ; Anastasie, Marie ; Archambault, Louis ; Ayot, Pierre ; Barbeau, Marcel ; Beaudin, Jean-Pierre ; Bellefleur, Léon ; Belzile, Louis ; Benoît, Jean ; Blair, Robert ; Boisvert, Gilles ; Borduas, Paul-Emile ; Bouchard, Mary S. ; Brandtner, Fritz ; Bruneau, Kittie ; Charbonneau, Monique ; Comtois, Ulysse ; Cournoyer, Serge ; Cozic, Yvon ; Daglish, Peter ; Dallaire, Jean ; Dallegret, François ; Daoust, Carl ; Daudelin, Charles ; Delavalle, Jean-Marie ; Derouin, René ; Dinel, Pierre-Roland ; Dulude, Claude ; Dumouchel, Albert ; Ewen, Paterson ; Ferron, Marcelle ; Filion, Gabriel ; Fortier, Ivanché ; Fortier, Michel ; Fortin, Marc-Aurèle ; Fox, John ; Gagnon, Charles ; Gaucher, Yves ; Gauguet-Larouche, Jean ; Gauvreau, Pierre ; Gervais, Lise ; Giguère, Roland ; Gnass, Peter ; Goguen, Jean ; Goodwin, Betty ; Heyvaert, Pierre ; Hurtubise, Jacques ; Jasmin, André ; Jauran ; Jérôme, Jean-Paul ; Juneau, Denis ; Lacroix, Richard ; Lajeunie, Jean-Claude ; Leclair, Michel ; Leduc, Fernand ; Leduc, Ozias ; Lemieux, Jean-Paul ; Lemoyne, Serge ; Leroy, Hugh ; Letendre, Rita ; Lyman, John ; Maltais, Marcelle ; Marion, Gilbert ; McEwen, Jean ; McLaren, Norman ; Merola, Mario ; Molinari, Guido ; Montpetit, André ; Montpetit, Guy ; Mousseau, Jean-Paul ; Muhlstock, Louis ; Noël, Jean ; Parent, Mimi ; Pellan, Alfred ; Pichet, Roland ; Riopelle, Jean-Paul ; Roberts, Goodridge ; Roussil, Robert ; Savoie, Robert ; Saxe, Henry ; Scott, Marian ; Smith, Jori ; Soucy, François ; Steinhouse, Tobie ; Sullivan, Françoise ; Surrey, Philip ; Tétreault, Pierre-Léon ; de Tonnancour, Jacques ; Toupin, Fernand ; Tousignant, Claude ; Tousignant, Serge ; Tremblay, Gérard ; Trudeau, Yves ; Vaillancourt, Armand ; Vilder, Roger ; Villeneuve, Arthur ; Wainwright, Robert Barry
biog., tent. p. 73-121
Frans & Engels
Trois générations d'art québécois 1940-1950-1960, Musée d'Art Contemporain, Montréal 30.06 - 01.09.1976
boek
Keywords: Canada; Québec